8
$\begingroup$

Let $a,b,c$ be the lengths of the sides of a triangle. The area is given by Heron's formula:

$$A = \sqrt{p(p-a)(p-b)(p-c)},$$

where $p$ is half the perimeter, or $p=\frac{a+b+c}{2}$.

Could you please provide the proof of this formula?

Thank you in advance.

$\endgroup$
5
$\begingroup$

A simple derivation exploits the cosine theorem. We have $\Delta=\frac{1}{2}ab\sin C$, hence $$ 4\Delta^2 = a^2 b^2 \sin^2 C = a^2 b^2 (1-\cos C)(1+\cos C).\tag{1}$$ On the other hand, $ 2ab\cos C = a^2+b^2-c^2$, hence $$ 2ab(1+\cos C) = (a+b)^2-c^2 = (a+b+c)(a+b-c), \tag{2}$$ $$ 2ab(1-\cos C) = c^2-(a-b)^2 = (a-b+c)(-a+b+c),\tag{3}$$ and by multiplying $(2)$ and $(3)$ and exploiting $(1)$ $$ 16\Delta^2 = (a+b+c)(-a+b+c)(a-b+c)(a+b-c)\tag{4} $$ which is equivalent to $$ \Delta = \sqrt{s(s-a)(s-b)(s-c)}\tag{5} $$ as wanted.


Alternative derivation: by considering the circumcenter $O$ and its distances from the sides we have $$2\Delta = R\sum_{cyc}a\cos A,\qquad 16\Delta^2 = \sum_{cyc}a^2\cdot 2bc(\cos A)=\sum_{cyc}a^2(b^2+c^2-a^2)\tag{6}$$ through $4R\Delta=abc$ and the cosine theorem. By rearranging the RHS of $(6)$ $$ 16\Delta^2 = (a^2+b^2+c^2)^2-2(a^4+b^4+c^4)\tag{7} $$ immediately follows.

$\endgroup$
4
$\begingroup$

It is actually quite simple. Especially if you allow using trigonometry, which, judging by the tags, you do. If $\alpha$ is the angle between sides $a$ and $b$, then it is known that $$ \begin{align} A &= \frac{ab\sin \alpha}{2},\\ A^2 &= \frac{a^2b^2\sin^2 \alpha}{4}. \end{align} $$ Now, $\sin^2 \alpha = 1 - \cos^2 \alpha$, and you can find $\cos \alpha$ from the law of cosines: $$ c^2 = a^2 + b^2 - 2ab \cos \alpha. $$

You just find $\cos \alpha$ from this equality, plug it into the formula for $A$ above, and Heron's formula pops up as a result.

$\endgroup$
  • 1
    $\begingroup$ To avoid the calculations, see WolframAlpha. $\endgroup$ – user26486 Jun 24 '15 at 21:49
4
$\begingroup$

Nobody can provide the proof but many can provide a proof or perhaps many proofs.

Notice that the area must be a 2nd-degree homogeneous function of $a$, $b$, and $c$, for example, if you multiply $a$, $b$, and $c$ by $9$ then you multiply the area by $9^2=81$, etc.

Next, notice that the area must be $0$ if $a+b=c$: if the distance along one side plus the distance along another side is equal to the distance along the third side, then the three corners are on a straight line, so the area is $0$. For that reason $a+b-c$ should appear as a factor, i.e. as something you multiply by.

For the same reason, $b+c-a$ and $c+a-b$ should be factors.

Next, notice that if $a=b=c=0$, then the area must be $0$, so that's why $a+b+c$ should be a factor.

Now we have $(a+b+c)(a+b-c)(b+c-a)(c+a-b)$. That is homogeneous of degree $4$ rather than $2$, so take its square root and we have $\sqrt{(a+b+c)(a+b-c)(b+c-a)(c+a-b)}$, which is homogenous of degree $2$. That, then, should be proportional to the area.

Now let's see what the constant of proportionality is: The area of a right triangle with legs of length $1$ and hypotenuse of length $\sqrt2$ is $1/2$. Plugging in those three numbers for $a$, $b$, and $c$ we get $$ \frac 1 2 =\text{constant}\times\sqrt{\left(1+1+\sqrt 2\right) \left(1+1-\sqrt 2\right)\left(1-1+\sqrt 2\right)\left(-1+1+\sqrt2\right)} = \text{constant}\times 2. $$ So the "constant" is $\dfrac 1 4$ and finally we have $$ \text{area} = \frac 1 4 \sqrt{(a+b+c)(a+b-c)(b+c-a)(c+a-b)}. $$ That's Heron's formula.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.